PENGARUH PROFITABILITAS, LIKUIDITAS DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PADA TAHUN 2013 - 2017 - Widia Firta (Institut Pendidikan Tapanuli Selatan, 2021)
This study aims to analyze whether Profitability, Liquidity and Business Risk have a significant effect on the Capital Structure of Manufacturing Companies listed on the Indonesia Stock Exchange in 2013 - 2017. In this study, the data processed is data on Capital Structure, Profitability, Liquidity, and Business Risk in the ratio financial statements of Manufacturing Companies listed on the Indonesia Stock Exchange in 2013-2017. The method used in this study is descriptive statistical analysis method. The analytical tool used to measure the variables studied is by multiple linear regression analysis with t test, F test, and determination coefficient test. The software application used to analyze the data in this study is Eviews 9.The results of this study indicate that partially profitability has a negative and significant effect on capital structure. Liquidity partially has a negative and significant effect on capital structure. Business risk partially has a positive and significant effect on capital structure. Simultaneously Profitability, Liquidity and Business Risk, have a significant effect on Profitability. And based on the test of the coefficient of determination (R2) the value is quite high which means that the percentage contribution of the influence of independent variables is Profitability, Liquidity and Business Risk, to the Capital Structure. While the rest is explained by other variables not examined in this study.